2011
DOI: 10.1371/journal.pone.0029367
|View full text |Cite
|
Sign up to set email alerts
|

Granulysin-Expressing CD4+ T Cells as Candidate Immune Marker for Tuberculosis during Childhood and Adolescence

Abstract: BackgroundGranulysin produced by cytolytic T cells directly contributes to immune defense against tuberculosis (TB). We investigated granulysin as a candidate immune marker for childhood and adolescent TB.MethodsPeripheral blood mononuclear cells (PBMC) from children and adolescents (1–17 years) with active TB, latent TB infection (LTBI), nontuberculous mycobacteria (NTM) infection and from uninfected controls were isolated and restimulated in a 7-day restimulation assay. Intracellular staining was then perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
1
16
0
1
Order By: Relevance
“…Because CD8 + effector memory T cells that produce granulysin also express surface TNF-a, they are depleted by anti-TNF-a immunotherapy for autoimmune diseases, which may contribute to reactivation of TB in these individuals (109). Granulysin has also been detected in CD4 + T cells (110), and its expression in CD4 + T cells has been suggested as a marker of TB in children (111). Adults with active TB have been shown to have significantly lower circulating granulysin in their plasma compared to healthy controls.…”
Section: Cd8mentioning
confidence: 99%
“…Because CD8 + effector memory T cells that produce granulysin also express surface TNF-a, they are depleted by anti-TNF-a immunotherapy for autoimmune diseases, which may contribute to reactivation of TB in these individuals (109). Granulysin has also been detected in CD4 + T cells (110), and its expression in CD4 + T cells has been suggested as a marker of TB in children (111). Adults with active TB have been shown to have significantly lower circulating granulysin in their plasma compared to healthy controls.…”
Section: Cd8mentioning
confidence: 99%
“…While multifunctional CD4+ T cells simultaneously producing IFN-γ/TNFα/IL-2 are detectable in Mtb infection (24, 25), CD4+ T cells can also function as cytotoxic cells and produce anti-Mtb perforin and granulysin in vitro . Murine CD4+ T cells can directly kill Mtb-infected cells in vivo , although the mechanism remain unclear (26, 27). The role of IL-17- and IL-22-producing CD4+ T cells has been investigated in animal models and whether these cells are protective or detrimental needs to be further investigated(2830).…”
Section: Introductionmentioning
confidence: 99%
“…This improved mechanism of protection has also been demonstrated using antibody blockage of the granule exocytosis pathway, that dramatically reduced the lytic activity of T cells against Mtb-infected macrophages and the increase of intracellular growth of bacteria [28]. Similarly, granulysin expression by CD4 + memory T cells is a candidate immune marker for TB infection, notably, in childhood and adolescence [29] and CD4T cells expressing granulysin correlate with the clinical forms of leprosy [30]. Our own previous studies demonstrated significantly lower plasma granulysin levels in adults with active disease in highly endemic area in Indonesia, and in children with TB disease in Italy [31], which increased after completion of therapy.…”
Section: Discussionmentioning
confidence: 87%